Reaction wheel pendulum control using fourth‐order discontinuous integral algorithm - Gutiérrez‐Oribio, Diego; Mercado‐Uribe, Ángel; Moreno, Jaime A.; Fridman, Leonid (International journal of robust and nonlinear control, 2021)
Summary The fourth‐order model of the reaction wheel pendulum is considered and a fourth‐order discontinuous integral algorithm is used for stabilization and tracking of the system, using a continuous control signal. The states reach the origin or a reference signal in finite‐time, even in presence of uncertain control coefficient and a kind of matched and unmatched uncertainties/disturbances. A homogeneous Lyapunov function is designed to ensure local finite‐time stability of the system, which can be used for designing the controller gains. Simulations and experimental results illustrate the performance and advantages of the presented algorithm.